The More the Better—Lower Rate of Stage Migration and Better Survival in Patients With Retrieval of 20 or More Regional Lymph Nodes in Pancreatic Cancer: A Population-Based Propensity Score Matched and Trend SEER Analysis. Issue 5 (May 2017) - Warschkow, Rene; Widmann, Bernhard; Beutner, Ulrich; Marti, Lukas; Steffen, Thomas; Schiesser, Marc; Schmied, Bruno M.
Abstract : Objective: The aim of this study was to assess the influence of regional lymph node (RLN) retrieval on stage migration and survival in pancreatic cancer. Methods: A total of 7685 stage I and II pancreatic cancer patients were identified in the Surveillance, Epidemiology, and End Results database in 2004–2011. The impact of RLN was assessed using Cox regression, propensity score methods, and joinpoint regression. Results: In 3079 patients, 1 to 10 RLNs were retrieved; in 2799 patients, 11 to 19 RLNs, and in 1807 patients, 20+ RLNs. The rate of node-positive pancreatic cancer increased with the number of retrieved RLN. This trend continued beyond 10 retrieved RLN ( P < 0.001). In unadjusted analysis, retrieval of RLN did not influence survival ( P = 0.178). When adjusting for significant bias in staging variables ( P < 0.001), retrieval of 20+ RLNs compared to 11 to 19 RLNs was associated with an increased survival in node-negative (hazard ratio, 0.78; 95% confidence interval, 0.62–0.98; P = 0.033) and node-positive cancer (hazard ratio, 0.83; 95% confidence interval, 0.74–0.93; P = 0.002). Conclusions: This population-based propensity score–adjusted investigation demonstrated that more retrieved RLNs in pancreatic cancer decreases the rate of stage migration and improves the oncological outcome in node-negative and positive cancer. Contradictory results may be explained by a bias in the cancer characteristics for a different extent of RLN retrieval.